Pilonidal Sinus Excision Using Carbon Dioxide Laser 10600 nm - Albahadili, Muhammad A.; Awazli, Lutfi G. (Iraqi Journal of Laser, 2019)
The current standard for treating pilonidal sinus (PNS) is surgical intervention with excision of the sinus. Recurrence of PNS can be controlled with good hygiene and regular shaving of the natal cleft, laser treatment is a useful adjunct to prevent recurrence. Carbon dioxide (CO2) laser is a gold standard of soft tissue surgical laser due to its wavelength (10600 nm) thin depth (0.03mm) and collateral thermal zone (150mic).It effectively seals blood vessels, lymphatic, and nerve endings, Moreover wound is rendered sterile by effect of laser. Aim of this study was to apply and assess the clinical usefulness of CO2 10600nm laser in pilonidal sinus excision and decrease chance of recurrence. Design: For 10 patients, between 18 and 39 year old (28.5 ± 6.02), PNS excision under local anesthesia, using CO2 laser continuous mode, power 10 W, all cases closed primarily. Using laser system (KLS MARTIN 50plus, 10600nm). Results: no pain during operation but mild during first week, the operative field was dry, mild edema in 80% in 1st. Week, infection in one case, its excellent overall satisfaction throughout 2-4 weeks postoperative follow-up. Conclusion: The CO2 laser offers the following benefits; almost bloodless surgery; reduced risk of infection; less scarring; precisely controlled surgery, often faster than conventional approaches and therefore achieving short hospital stays.